2019
DOI: 10.1109/access.2019.2945422
|View full text |Cite
|
Sign up to set email alerts
|

Stacked Ensemble for Bioactive Molecule Prediction

Abstract: Bioactive molecular compounds are essential for drug discovery. The biological activity of these compounds needs to be predicted as this is used to determine the drug-target ability. As ineffective drugs are discarded after production, leading to resource and time wastage, it is important to predict bioactive molecules with models having high predictive performance. This study utilizes the stacked ensemble which uses the prediction of multiple base classifiers as features, used to train a meta classifier which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…However, these assays have yet to experimentally test a sufficient number of active or inactive compounds, therefore making the QSAR modeling challenging (e.g., 3 active compounds in [36]). On the other hand, we found that the size of our dataset, 70, is on par with other small-dataset QSAR studies (e.g., 16 in [19], and 48 in [20]); we thus believe this dataset has a sufficient number of data to build goodperforming QSAR models.…”
Section: A Datasetsmentioning
confidence: 60%
See 1 more Smart Citation
“…However, these assays have yet to experimentally test a sufficient number of active or inactive compounds, therefore making the QSAR modeling challenging (e.g., 3 active compounds in [36]). On the other hand, we found that the size of our dataset, 70, is on par with other small-dataset QSAR studies (e.g., 16 in [19], and 48 in [20]); we thus believe this dataset has a sufficient number of data to build goodperforming QSAR models.…”
Section: A Datasetsmentioning
confidence: 60%
“…Nonetheless, current 2D QSAR analysis often relies on training machine learning algorithms with a large-sized drug activity dataset (size > 1000) [6], [16], which requires significant time and effort on both benchwork and statistical analysis. For this reason, developing new drugs can cost hundreds of millions of U.S. dollars [17] and can take over a decade to transition to a marketable state [18].…”
Section: Introductionmentioning
confidence: 99%
“…The stacked ensemble (SE) learning was first demonstrated by Wolpert [40], where authors exhibited a stacked formation of strong and weak ML algorithms which could improvise framework accuracy and filter samples by boosting training competency and lessening overfitting issues. Several researchers have represented their approaches based on SE classification for numerous areas such as network intrusion detection (NID), statistics, forecasting big data, and human activity recognition [40,41]. The primary concept of SE architecture is the combination of weak ML algorithms to generate a strong framework.…”
Section: Stacked Ensemble (Se) Classifiermentioning
confidence: 99%
“…It is also used to yield poly (arylene-amine) from arylamines polymerisation [5], yield aryl and heteroaryl chlorides in an aqueous condition free from solvent [6], and synthesise iron (II) clathrochelate unit bearing secondary arylamine copolymers due to the strong compounds which it yields. Surveys carried out by Gómez-Bombarelli et al [7] and Rodrigues et al [8] shows that chemical space search and optimization, virtual screening, discovery of drug target, the prediction of protein structures, chemical properties, gene-gene interaction, bioactivity of molecules in a compound [9], and toxicity [10], are some of the ways predictive analysis has been applied to the vast data produced in biochemical studies [11].…”
Section: Introductionmentioning
confidence: 99%